Patient Safety Culture: the same functional typology, different cultures - Pedrosa, V. (2020)
Background: The safety culture of the patient can be a reality in health care if we all build it with daily steps. The challenge of the third millennium in patient safety lies in shifting proactive organizational culture that serenely analyzes failures, promotes learning, and minimizes the likelihood of repeat mistakes that we all obviously make. Cultural changes are not fast or simple, but must be fostered through education and training, a fair culture that examines events as opportunities, and assigns zero tolerance for rule-breaking and negligence and secrecy for transparency; centering the practice on the patient; changing the working models, where the patient is truly included (1,2,3,5,6, 10,12, 13,14,15, 17, 18, 19, 21, 26). Fostering a culture of safety in health organizations should begin by evaluating the current culture. In Primary Health Care, patient safety becomes more important because a considerable proportion of safety incidents detected in hospitals originate from earlier levels of the system, most of the interactions, and the largest volume of consultations in the functional units at this level of health care in family health units that provide accessible care, global and longitudinal follow-up on the health process in a lifetime, enabling greater health gains, and greater proximity to the patient. They are elementary health care units, based on multiprofessional teams, made up of doctors, nurses and administrative staff. Still, many are on very different levels in terms of safety culture of the patient, although in all, the patient wants to have security (4, 8, 9, 11, 15, 16, 19, 20, 22, 23, 24, 25). A cultura de segurança do doente pode ser uma realidade nos cuidados de saúde se todos a construirmos com passos diários. O desafio do terceiro milénio em segurança do doente reside na mudança da cultura organizacional proativa que analise serenamente as falhas, promova a aprendizagem e minimize a probabilidade de repetição de erros que obviamente todos fazemos. As mudanças culturais não são rápidas nem simples, mas deve fomentar-se através da educação e formação, uma cultura justa que examina os eventos como oportunidades, e atribui tolerância zero à violação de regras e à negligência e do secretismo para a transparência; centrando a prática no doente; alterando os modelos de trabalho, onde se inclui verdadeiramente o doente (1,2,3,5,6, 10,12, 13,14,15, 17, 18, 19, 21, 26). Fomentar uma cultura de segurança nas organizações de saúde, deve começar por avaliar a cultura vigente. Nos Cuidados de Saúde Primários, a segurança do doente assume uma maior importância pois, uma proporção considerável de incidentes de segurança detetados nos hospitais têm origem em níveis anteriores do sistema, a maioria das interações e o maior volume de consultas, nas unidades funcionais deste nível de cuidados de saúde, nas unidades de saúde Familiar que oferecem cuidados acessíveis, acompanhamento global e longitudinal no processo de saúde numa vida, possibilitando maiores ganhos em saúde, e uma maior proximidade ao doente. São unidades elementares de prestação de cuidados de saúde, assentes em equipas multiprofissionais, constituídas por médicos, por enfermeiros e por pessoal administrativo. Ainda assim, muitas estão em patamares muito distintos em matéria de cultura de segurança do doente, apesar de em todas, o doente querer ter segurança (4, 8, 9, 11, 15, 16, 19, 20, 22, 23, 24, 25). Goal: Describe the patient's safety culture of health professionals from two family health units belonging to the same Health Center, in order to understand the similarities and/or differences between the two. Descrever a cultura de segurança do doente dos profissionais de saúde de duas unidades de saúde familiar que pertencem ao mesmo Centro de Saúde, de modo a compreender as semelhanças e/ou diferenças entre ambas. Method: Qualitative study, semi-structured interview, carried out (GPs and nurses), which constitute 2 USF (models A and B) of 1 Health Center in the Lisbon area. Content analysis was supported by maturity levels in a patient safety culture, five maturity levels ranging from 1 (worst culture) to 5 (best culture). Unit model A-8 nurses and 5 GP and unit model B-6 nurses and 6 GP (Kirk et al, 2007) (14) Results: By adjusting the responses within a maturity level of patient safety culture to the 2 functional units, it was observed that culture oscillated between 1.8 values in the USF model A, close to a reactive culture, in which the organization only cares about safety when they occur problems and 4 values of USF B, close to a proactive culture, with patient safety measures, even without adverse events, close to the ideal, with a sensitized and worried team. Ajustando, as respostas enquadráveis num nível de maturidade de CSD às 2 unidades funcionais, percebeu-se que cultura oscilou entre 1,8 valores na USF modelo A, próxima de uma cultura reativa, em que a organização só se preocupa com a segurança quando ocorrem problemas e 4 valores dad A USF B, próxima de uma cultura proativa, com medidas de segurança do doente, mesmo sem ocorrerem eventos adversos, próxima do ideal, com uma equipa sensibilizada e preocupada. Conclusion: As unidades funcionais têm a mesma tipologia, pertencem ao mesmo Centro de Saúde, mas alinham a cultura de segurança do doente à sua maior e menor complexidade, respetivamente modelo B e A. Ou seja, não se observa a segurança do doente sob o mesmo chapéu, apesar de se atuar na mesma área geográfica. Falta mais e melhor avaliação, informação e formação para que, a cultura de segurança do doente se nível e não dependa do nível organizativo pois, para os doentes desta zona geográfica, virar à direita ou à esquerda pode transformar a segurança dos cuidados de saúde recebidos pelo doente, oferecidos ao cidadão (1,2,3.4,5, 6, 7, 8, 9, 11, 15, 16, 19, 20, 22, 23, 24, 25). The functional units have the same typology, belong to the same Health Center, but align the patient's safety culture with its greater and lesser complexity, respectively, model B and A. In other words, patient safety is not observed under the same hat, although it operates in the same geographical area. There is a need for more and better evaluation, information and training so that the safety culture of the patient is level and not dependent on the organizational level because, for patients in this geographical area, turning right or left can transform the safety of the health care received by the patient, offered to the citizen (1,2,3.4,5, 6, 7, 8, 9, 11, 15, 16, 19, 20, 22, 23, 24, 25).